Levels of wound calprotectin and other inflammatory biomarkers aid in deciding which patients with a diabetic foot ulcer need antibiotic therapy (INDUCE study). Issue 2 (15th August 2017) - Ingram, J. R.; Cawley, S.; Coulman, E.; Gregory, C.; Thomas‐Jones, E.; Pickles, T.; Cannings‐John, R.; Francis, N. A.; Harding, K.; Hood, K.; Piguet, V.
Abstract: Aims: Deciding if a diabetic foot ulcer is infected in a community setting is challenging without validated point‐of‐care tests. Four inflammatory biomarkers were investigated to develop a composite algorithm for mildly infected diabetic foot ulcers: venous white cell count, C‐reactive protein (CRP) and procalcitonin, and a novel wound exudate calprotectin assay. Calprotectin is a marker of neutrophilic inflammation. Methods: In a prospective study, people with uninfected or mildly infected diabetic foot ulcers who had not received oral antibiotics in the preceding 2 weeks were recruited from community podiatry clinics for measurement of inflammatory biomarkers. Antibiotic prescribing decisions were based on clinicians' baseline assessments and participants were reviewed 1 week later; ulcer infection was defined by clinicians' overall impression from their two assessments. Results: Some 363 potential participants were screened, of whom 67 were recruited, 29 with mildly infected diabetic foot ulcers and 38 with no infection. One participant withdrew early in each group. Ulcer area was 1.32 cm 2 [interquartile range (IQR) 0.32–3.61 cm 2 ] in infected ulcers and 0.22 cm 2 (IQR 0.09–1.46 cm 2 ) in uninfected ulcers. Baseline CRP for mild infection was 9.00 mg/ml and 6.00 mg/ml for uninfected ulcers; most procalcitonin levels were undetectable. Median calprotectin level in infected diabetic foot ulcers was 1437 ng/ml and 879 ng/ml in uninfected diabetic foot ulcers. Area under the receiver operating characteristic curve for a composite algorithm incorporating calprotectin, CRP, white cell count and ulcer area was 0.68 (95% confidence intervals 0.52–0.82), sensitivity 0.64, specificity 0.81. Conclusions: A composite algorithm including CRP, calprotectin, white cell count and ulcer area may help to distinguish uninfected from mildly infected diabetic foot ulcers. Venous procalcitonin is unhelpful for mild diabetic foot ulcer infection. What's new?: Distinguishing between mild infection and no infection in diabetic foot ulcers, a frequent position of equipoise in antibiotic prescribing, is challenging in the absence of objective evidence available at point of care. We developed a novel wound exudate calprotectin assay which, when combined with venous C‐reactive protein, white cell count and ulcer area, provided a diagnostic algorithm for diabetic foot ulcer infection. The combined algorithm has a specificity of 0.81 in distinguishing mild infection from no infection in a diabetic foot ulcer.